2014
DOI: 10.17713/ajs.v43i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Integration for Solving Large Data Reconciliation Problems

Abstract: Macro-integration technique is a well established method for<br />reconciliation of large, high-dimensional tables, especially applied to macroeconomic data at national statistical oces (NSO). This technique is mainly used when data obtained from dierent sources should be reconciled on a macro level. New areas of applications for this technique arise as new data sources become available to NSO's. Often these new data sources cannot be combined on a micro level, while macro integration could provide a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Boonstra et al () showed that the GREG‐estimator used for repeated weighting is equivalent to a weighted least squares estimate, where consistency under linear constraints should be achieved. The repeated weighting solution can be obtained as a solution to a specific quadratic optimization problem as in (1), after choosing a particular specification for the weights; see, for example, the work of Mushkudiani, Daalmans, and Pannekoek ().…”
Section: Population Census 2011mentioning
confidence: 99%
“…Boonstra et al () showed that the GREG‐estimator used for repeated weighting is equivalent to a weighted least squares estimate, where consistency under linear constraints should be achieved. The repeated weighting solution can be obtained as a solution to a specific quadratic optimization problem as in (1), after choosing a particular specification for the weights; see, for example, the work of Mushkudiani, Daalmans, and Pannekoek ().…”
Section: Population Census 2011mentioning
confidence: 99%